2016
DOI: 10.4178/epih.e2016030
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological analysis of acute flaccid paralysis in Khuzestan Province, southwest Iran, from 2006 to 2010

Abstract: OBJECTIVES:Investigations into the epidemiology of acute flaccid paralysis (AFP) are an essential strategic component of the Global Poliomyelitis Eradication Initiative of the World Health Organization (WHO), and are part of the certification process for polio eradication worldwide. This is an epidemiological report of AFP incidence in children less than 15 years old in southwest Iran.METHODS:This was a retrospective cohort study, carried out based on WHO guidelines, in which we reviewed non-polio AFP cases re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
3
11
0
Order By: Relevance
“…Almost half of the patients (49.7%) had fever, and approximately one-third of the patients had asymmetric paralysis. This finding is similar to that in Iran [10]. Odoom et al [13] reported that 84.2% of cases had fever and 64.8% had asymmetric paralysis, and another study in Turkey reported that 13.6% of the total cases had fever [15].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Almost half of the patients (49.7%) had fever, and approximately one-third of the patients had asymmetric paralysis. This finding is similar to that in Iran [10]. Odoom et al [13] reported that 84.2% of cases had fever and 64.8% had asymmetric paralysis, and another study in Turkey reported that 13.6% of the total cases had fever [15].…”
Section: Discussionsupporting
confidence: 85%
“…However, importation of poliovirus remains a potential threat; therefore, it is essential to continue AFP surveillance. The study reported that half of the reported cases were of patients below 5 years of age, which is consistent with findings of a study conducted in Iran [10] and another one in Bangladesh [11]. However, higher percentages were reported in countries such as Congo (85.2%) [12] and Ghana (74.4%) [13], and lower percentages were reported in other countries including Italy (37%) [14].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The most common cause of acute flaccid paralysis worldwide is Guillain Barre Syndrome (2). While some cases can be severe, rapidly progressive and life threatening; prompt supportive treatment with immunotherapy can be effective (10).…”
Section: Discussionmentioning
confidence: 99%
“…Guillain–Barre' syndrome (GBS) is an acute inflammatory polyneuropathy, characterized by possibly progressive, essentially symmetric, weakness and areflexia; with possible sensory disturbance in a previously well child (1). With an incidence of 4 per 100,000 per year, it is the most common cause of acute flaccid paralysis worldwide since the eradication of poliomyelitis and can affect all age groups (2).…”
Section: Introductionmentioning
confidence: 99%